Study Quenching Process on Rubber Tapping Knives Home Production - Gunawan, Indra; Effendi, Sairul; Pratama, Dioni Yoga (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2026)
The rubber tapping knives were often produced by blacksmiths experience cracks and chips or even break on the blade, so rubber farmers have to frequently replace them with new knives. Thus, the product cannot be used for a long time and its economic value is reduced. The reason why the rubber tapping knives made by blacksmiths are easily damaged is because the plating method on the product is not carried out correctly. So that the resulting product has a relatively low level of hardness. This study aims to determine the effect of the hardening and quenching processes on the hardness of rubber tapping knives made by blacksmiths. The test data were analyzed using ANOVA with a full factorial level design, a main effect model design, and 3 replications assisted by Design-Expert software. At a temperature of 800℃ the maximum hardness value of 62.8 HRC was obtained from the quenching results using water cooling media, while the minimum hardness value of 62.2 HRC was obtained from oil cooling media. At a temperature of 850℃, the maximum hardness value of 60.4 HRC was obtained from quenching using water cooling media, and the minimum hardness value was obtained from oil cooling media of 59.1 HRC